The Concept of Tumbuk in Javanese Gamelan Tuning - Harmanto Harmanto; Suyoto Suyoto; Jody Diamond (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
This study aimed to reveal the concept of Tumbuk in Javanese gamelan tuning, namely gamêlan agêng with Sléndro and Pélog. This study used a qualitative method with an ethical emic perspective. The data collection was done by conducting literature review, observation, interviews, and studio work, then processed with data analysis. The data analysis then was followed up through data interaction by interpreting the relationship reactions of the three elements of analysis consisting of data collection, data reduction, and data presentation. The interpretation of the data was done inductively, so that the conclusion was drawn entirely from the development of the data according to the realities of the field. The results showed that tumbuk was not only limited to a note that has the same high and low, but it is a musical concept that integrates the Sléndro and Pélog scales in the tuning of a set of gamelans. There are basically only two types of tumbuk: nêm tumbuk and lima tumbuk. Other than those, it means that they are the strut. The thing is,tumbuk has a central tone that serves as a benchmark and a supporting tone whose position strengthens the integration of each type of tumbuk. As a concept, it was found that tumbuk plays several important roles including equalizing the highs and lows of certain notes, equalizing the range of certain notes, and conditioning the range of notes or the addition of the tune.